Comparative Genomics of Bacillus amyloliquefaciens Strains Reveals a Core Genome with Traits for Habitat Adaptation and a Secondary Metabolites Rich Accessory Genome - Belbahri, Lassaad; Chenari Bouket, Ali; Rekik, Imen; Alenezi, Faizah N.; Vallat, Armelle; Luptakova, Lenka; Petrovova, Eva; Oszako, Tomasz; Cherrad, Semcheddine; Vacher, Sébastien; Rateb, Mostafa E. (Frontiers in Microbiology, 2017)
The Gram positive, non-pathogenic endospore-forming soil inhabiting prokaryote Bacillus amyloliquefaciens is a plant growth-promoting rhizobacterium. Bacillus amyloliquefaciens processes wide biocontrol abilities and numerous strains have been reported to suppress diverse bacterial, fungal and fungal-like pathogens. Knowledge about strain level biocontrol abilities is warranted to translate this knowledge into developing more efficient biocontrol agents and bio-fertilizers. Ever-expanding genome studies of B. amyloliquefaciens are showing tremendous increase in strain-specific new secondary metabolite clusters which play key roles in the suppression of pathogens and plant growth promotion. In this report, we have used genome mining of all sequenced B. amyloliquefaciens genomes to highlight species boundaries, the diverse strategies used by different strains to promote plant growth and the diversity of their secondary metabolites. Genome composition of the targeted strains suggest regions of genomic plasticity that shape the structure and function of these genomes and govern strain adaptation to different niches. Our results indicated that B. amyloliquefaciens: i) suffer taxonomic imprecision that blurs the debate over inter-strain genome diversity and dynamics, ii) have diverse strategies to promote plant growth and development, iii) have an unlocked, yet to be delimited impressive arsenal of secondary metabolites and products, iv) have large number of so-called orphan gene clusters, i.e. biosynthetic clusters for which the corresponding metabolites are yet unknown, and v) have a dynamic pan genome with a secondary metabolite rich accessory genome.